Development of a novel red-emitting cesium hafnium iodide scintillator. (May 2019) - Kodama, Shohei; Kurosawa, Shunsuke; Ohno, Maki; Yamaji, Akihiro; Yoshino, Masao; Pejchal, Jan; Král, Robert; Ohashi, Yuji; Kamada, Kei; Yokota, Yuui; Nikl, Martin; Yoshikawa, Akira
Abstract: Cesium hafnium iodide (CHI) was reported as a novel red-emitting scintillator in our previous article, while optimization of the crystal quality and evaluation of the scintillation performance were insufficient. In this study, a large and transparent CHI single crystalline specimen was obtained using slow crystal growth speed. Coupled with a Si avalanche photo-diode, the full width at half maximum energy resolution was evaluated to be 4.2 ± 0.2% at 662 keV which was the best value among conventional red-emitting scintillators. The scintillation light output, non-proportional response of light output and scintillation decay were also evaluated with a photomultiplier tube. Highlights: Cs2 HfI6 scintillator was grown by the vertical Bridgman-Stockberger method. Transparent single crystal was obtained at a slower growth speed than previous report. Pulse height spectra and scintillation decay were measured. The FWHM energy resolution was estimated to be 4.2 ± 0.2% at 662 keV.